A comparative study between traditional topology optimization and lattice optimization for additive manufacturing. Issue 6 (19th December 2019) - Tyflopoulos, Evangelos; Steinert, Martin
Abstract: Topology optimization (TO) aids designers to come up with new ideas that would be impossible to be designed without this technology. However, the optimized results are usually characterized by high geometric complexity, which makes almost impossible their manufacturing by conventional methods. Additive manufacturing (AM) overcomes this problem and increases the design flexibility. In addition, lattice structures with their porous infill combine the design flexibility with good material properties, such as high strength compared with relatively low mass. In this paper, the authors compare designs derived from traditional TO lattice optimization with respect to their tensile strength. A case study of a custom cylindrical model is used to support the theory and collect empirical data. The simulation data as well as the implemented methodology in this work can be used as a guidance for the designers looking for new lightweight design ideas for AM.